Analisis Permohonan Pendaftaran Merek Secara Internasional Bagi UMKM Setelah Diterbitkan Peraturan Presiden No. 92 Tahun 2017 Tentang Ratifikasi Protokol Madrid - Yohanes Adi Putra Mahardika; Irna Nurhayati (Fakultas Hukum Universitas Islam Indonesia, 2019)
This research aims to analyze the barriers to the application of international trademark registration for MSME after the issuance of Presidential Regulation No. 92 of 2017 concerning Ratification of Madrid Protocols. Another purpose of this research is to find out the government's efforts in facing obstacles to international brand registration applications for MSMEs.This research is a normative legal research using primary data and secondary data. Primary data was collected through interviews with the guidelines of the interview, while secondary data obtained through the method of documentation with a study of the documentation and data analysis done qualitatively.The results of this study are: First, there are obstacles to the application of international trademark registration for MSMEs after the issuance of Presidential Regulation No. 92 of 2017 concerning the Ratification of the Madrid Protocol because of the lack of interest and insight of MSMEs on international trademark registration applications, general regulations, language difficulties, and the cost of expensive brand registration applications. Second, the efforts made by the government to face obstacles for MSMEs are by making rules for reducing the cost of applying for basic brand registration, the existence of a special team of the Madrid Protocol and increasing socialization of brands and applications for trademark registration using the Madrid Protocol.